Brain Drain from Turkey: Return Intentions of Skilled Migrants - Nil Demet Güngör; Aysit Tansel (Turkish Economic Association, 2010)
The study estimates an empirical model of return intentions using a dataset compiled from an internet survey of Turkish professionals residing abroad. In the migration literature, wage differentials are often cited as an important factor explaining skilled migration. The findings of our study suggest, however, that non-pecuniary factors, such as the importance of family and social considerations, are also influential in the return or non-return decision of the highly educated. In addition, economic instability in Turkey, prior intensions to stay abroad and work experience in Turkey also increase non-return. Female respondents also appear less likely to return indicating a more selective migration process for females.
Keywords: J64; F20; F22; 330; skilled migration; brain drain; return intentions; Turkey; Brain Drain; Rückwanderung; Motivation; Hochqualifizierte Arbeitskräfte; Türkei